Further Discourses on the Legal Nature of “Virtual Currency” Under Comparative Property Law - Nam, Do Giang; Khoi, Dao Trong (VNU Journal of Science: Legal Studies, 2021)
From the perspective of comparative property law, the article examines the precedents and official legal views on "virtual currencies" in countries representing both Common Law tradition (England, the United States) and Civil Law tradition (Pandectists/Germantic school including German, Japan, the Netherlands and Romanistic school including France) to identify the legal nature of “virtual currencies”. It concludes that although it is still controversial to classify “virtual currencies” into the available classes of property, most of these countries recognise “virtual currencies” as property and proceed to regulate them effectively. However, “virtual currency” should be considered a “non-traditional” property - a crypto asset created by a combination of blockchain technology and cryptographic techniques aimed at ensuring authenticity in confirming certain rights and interests of a legal subject. In the future, traditional concepts and principles of property law also need to be modernised to meet the requirements of diversifying new forms of non-traditional property in the era of the Fourth Industrial Revolution.